Application of plants extracts as green corrosion inhibitors for steel in concrete - a review - Panca Asmara, Yuli; Kurniawan, Tedi; Edy Sutjipto, Agus Geter; Jafar, Jamiluddin (Jurnal UPI, 2018)
High requirements in protection of steel reinforcing bar (steel rebar) from corrosion are necessary since there are multi interaction of corrosive chemicals which cause early damage of concrete buildings. Corrosion of steel in concrete can destroy the concretes and reduce concrete strength. To protect rebar from corrosion, application of corrosion inhibitor is believed to have higher performance compared to other protection systems. To date, organic inhibitors have promising methods in steel rebar protection as they are environment-friendly, compatible with concrete, cost effective and applicable in any various concrete conditions. Thus, demands in using these inhibitors tend to increase significantly. This paper reviews the applications of green corrosion inhibitor specifically highlighted in protecting mechanisms, typical plants extracted, performance in corrosion protection, and classification of green corrosion inhibitors. The corrosion resistances of carbon steels in concrete protected by green inhibitors are in focus. As summary, it can be confidently notified that green corrosion inhibitors for steel in concrete will have a prospect to be used as corrosion prevention in the future with further improvements.